Using critical information to strengthen pandemic preparedness: the role of national public health agencies. Issue 9 (29th September 2020) - Khan, Mishal S; Dar, Osman; Erondu, Ngozi A; Rahman-Shepherd, Afifah; Hollmann, Lara; Ihekweazu, Chikwe; Ukandu, Okechukwu; Agogo, Emmanuel; Ikram, Aamer; Rathore, Tayyab Razi; Okereke, Ebere; Squires, Neil
Abstract : COVID-19 has demonstrated that most countries' public health systems and capacities are insufficiently prepared to prevent a localised infectious disease outbreak from spreading. Strengthening national preparedness requires National Public Health Institutes (NPHIs), or their equivalent, to overcome practical challenges affecting timely access to, and use of, data that is critical to preparedness. Our situational analysis in collaboration with NPHIs in three countries—Ethiopia, Nigeria and Pakistan—characterises these challenges. Our findings indicate that NPHIs' role necessitates collection and analysis of data from multiple sources that do not routinely share data with public health authorities. Since initiating requests for access to new data sources can be a lengthy process, it is essential that NPHIs are routinely monitoring a broad set of priority indicators that are selected to reflect the country-specific context. NPHIs must also have the authority to be able to request rapid sharing of data from public and private sector organisations during health emergencies and to access additional human and financial resources during disease outbreaks. Finally, timely, transparent and informative communication of synthesised data from NPHIs will facilitate sustained data sharing with NPHIs from external organisations. These actions identified by our analysis will support the availability of robust information systems that allow relevant data to be collected, shared and analysed by NPHIs sufficiently rapidly to inform a timely local response to infectious disease outbreaks in the future.